La ville italienne dans l’œuvre de Jean-Philippe Toussaint : de “non-ville” à “mi-ville” - Maria Giovanna Petrillo (MediAzioni)
This study proposes to trace the changing representation of the Italian city in Toussaint’s novels, in perpetual flux, unfinished by definition and constantly surprising. In fact, if the narrator of the first part of Jean-Philippe Toussaint’s literary production seems to choose Italian metropolises that are ‘without qualities’, we can, however, highlight a turning point in his novelistic production that matches the evolution of the representation of the Italian city.